2016
DOI: 10.2217/fmb-2016-0115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Automated Becton Dickinson MAX Real-Time PCR Platform for Detection of Pneumocystis Jirovecii

Abstract: The quantitative BD MAX real-time PCR is a rapid and highly sensitive modality for detecting P. jirovecii, especially in samples from bronchoalveolar lavage fluid/bronchial washing fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…To discriminate cases of PCP (PCP + ) from colonization (PCP − ), we applied retrospective case-criteria in line with the European Conference on Infections in Leukaemia (ECIL) guidelines [ 13 ] with the available data. According to previous studies, we considered that C T values above 35 corresponded to colonization and not overt PCP [ 12 , 14 ] regardless of the host’s HIV status. Thus, the criteria for PCP + among our PCR-positive cohort were i) positive DIF and/or ii) C T value below 36.…”
Section: Methodsmentioning
confidence: 99%
“…To discriminate cases of PCP (PCP + ) from colonization (PCP − ), we applied retrospective case-criteria in line with the European Conference on Infections in Leukaemia (ECIL) guidelines [ 13 ] with the available data. According to previous studies, we considered that C T values above 35 corresponded to colonization and not overt PCP [ 12 , 14 ] regardless of the host’s HIV status. Thus, the criteria for PCP + among our PCR-positive cohort were i) positive DIF and/or ii) C T value below 36.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, a few studies have observed higher fungal detection rates in BAL fluids than in URT samples [222324]. However, information regarding the yield obtained from different LRT sample types is limited, particularly in non-HIV immunocompromised patients [2526]. Alanio et al [26] reported that fungal burdens did not significantly differ between BAL fluids and induced sputum; however, we demonstrated low detection rates from sputum/ETA samples compared with BAL samples.…”
Section: Discussionmentioning
confidence: 52%
“…Expectorated sputum or bronchoscopic samples (washing or bronchoalveolar lavage) were examined by qPCR in an automated Becton Dickinson MAX real-time PCR platform (Becton Dickinson, Diagnostic Systems, Sparks, MD, USA) 16. The primer sequences for the PJ target gene, major surface glycoprotein ( MSG ), were MSG-fw, 5ʹ-GAATGCAAATCCTTACAGACAG-3ʹ, and MSG-rv, 5ʹ-AAATCATGAACGAAATAACCATTGC-3ʹ.…”
Section: Methodsmentioning
confidence: 99%
“…A lower Ct value correlates with a higher PJ fungal burden. According to previous studies, a qPCR Ct value higher than 35, correlates with a clinically low PJ fungal burden and colonization 16,17. Thus, patients with a Ct value above 35 were excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation